Landschaftsarchäologie am DAI - Schultze, Erdmute (e-Forschungsberichte des DAI, 2017)
The working group for landscape archaeology at the German Archaeological Institute (LAAD) aims to give a forum for the exchange and discussion of the methods and theories in this field. Landscape archaeology research with its special methods is of growing importance for a number of projects in several departments of the institute. Two meetings held in 2015 were the third and fourth workshop of this group at all. The third LAAD-meeting in Rome involved a methodological workshop about aerial surveys with UAV systems and an introduction in structure from motion technology. The fourth LAAD-meeting took place in cooperation with the DLR Earth Observation Center (EOC) in Oberpfaffenhofen and was focused on the possibilities for using of earth observation data for archaeological research and heritage management.